PENGARUH KONSUMSI JUS TOMAT (SOLANUM LYCOPERSICUM) TERHADAP PENINGKATAN KADAR HEMOGLOBIN IBU HAMIL ANEMIA DI PUSKESMAS NGORO KABUPATEN JOMBANG - Sukati Sarmin; Arista Kusuma Wardani; Zeny Fatmawati; Elis Fatmawati (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2025)
Introduction: Anemia ranks second as the most common cause of maternal mortality after postpartum hemorrhage. Anemia rates vary across ASEAN countries, with Indonesia at around 73.2%, the Philippines at 58%, Thailand at 48%, and Malaysia at 35%. The impact of anemia on pregnancy varies from mild complaints to pregnancy complications. Anemia can be treated non-pharmacologically by consuming tomatoes. Objective: This study aims to determine the effect of tomato juice (Solanum Lycopersicum) consumption on increasing hemoglobin levels in anemic pregnant women at the Ngoro Health Center in Jombang District. Method: This study is a pre-experimental study using a one-group pre-post test design. The study population consisted of 43 pregnant women with anemia, with a sample size of 33 pregnant women who met the criteria set by the researcher. The sampling technique used was purposive sampling. Data analysis was performed using the dependent t-test. Results: The results of data analysis using the paired sample t-test showed a significant difference in hemoglobin levels before and after the intervention. The t-value of -10.119 indicates that the hemoglobin level after the intervention was higher than before. The p-value (Asymp. Sig. 2-tailed) of 0.000 is less than the significance level of 0.05 (p < 0.05), which means that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Conclusion: The administration of Fe tablets combined with tomato juice for seven consecutive days was effective in increasing hemoglobin levels in anemic pregnant women. The average hemoglobin level increased from 9.83 g/dL to 11.4 g/dL